2006
DOI: 10.1371/journal.pgen.0020129
|View full text |Cite
|
Sign up to set email alerts
|

The Uncoupling Protein 1 Gene (UCP1) Is Disrupted in the Pig Lineage: A Genetic Explanation for Poor Thermoregulation in Piglets

Abstract: Piglets appear to lack brown adipose tissue, a specific type of fat that is essential for nonshivering thermogenesis in mammals, and they rely on shivering as the main mechanism for thermoregulation. Here we provide a genetic explanation for the poor thermoregulation in pigs as we demonstrate that the gene for uncoupling protein 1 (UCP1) was disrupted in the pig lineage. UCP1 is exclusively expressed in brown adipose tissue and plays a crucial role for thermogenesis by uncoupling oxidative phosphorylation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 12 publications
2
129
0
1
Order By: Relevance
“…The latter used pigs as their subjects, whereas the former made use of rats. According to previous research, uncoupling protein 1 (UCP-1) is non-functional in pigs (45)(46). Since this non-functionality of UCP-1 appears not to be harmful in pigs, it could be said that irisin influences energy metabolism in pigs including signaling which is different from that in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The latter used pigs as their subjects, whereas the former made use of rats. According to previous research, uncoupling protein 1 (UCP-1) is non-functional in pigs (45)(46). Since this non-functionality of UCP-1 appears not to be harmful in pigs, it could be said that irisin influences energy metabolism in pigs including signaling which is different from that in rats.…”
Section: Discussionmentioning
confidence: 99%
“…During early mammalian evolution, UCP1 developed rapidly (Saito et al, 2008) from a probably nonthermogenic protoUCP1 that is still found in fish (Jastroch et al, 2005;Jastroch et al, 2007). UCP1 is principally found in all mammals -with the pig family being the only exception (Berg et al, 2006). Pigs have secondarily lost the ability to express UCP1 and are thus incapable of nonshivering thermogenesis (Mount, 1968).…”
Section: The Mechanism Of Heat Production In Brown Adipose Tissuementioning
confidence: 99%
“…This due to an open reading frame on the BAT-specific uncoupling protein 1 (UCP1) gene in the porcine species meaning that UCP1 is not expressed (Berg et al 2006). However, it has more recently been suggested that BAT is present in young piglets because of the different morphological appearances of adipocytes within perirenal adipose tissue in 2-week-old females (Attig et al 2008).…”
Section: Thematic Researchmentioning
confidence: 99%
“…In pigs, however, it has long been considered that BAT is not present (Trayhurn et al 1989) and the newborn is primarily dependent on shivering thermogenesis in muscle in order to prevent hypothermia at birth (Symonds & Lomax 1992). This due to an open reading frame on the BAT-specific uncoupling protein 1 (UCP1) gene in the porcine species meaning that UCP1 is not expressed (Berg et al 2006). However, it has more recently been suggested that BAT is present in young piglets because of the different morphological appearances of adipocytes within perirenal adipose tissue in 2-week-old females (Attig et al 2008).…”
Section: Introductionmentioning
confidence: 99%